DETERMINATION OF ELIGIBILITY ZAKAT RECIPIENTS USING ANALYTIC HIERARCHY PROCESS FOR UNIVERSITI TEKNOLOGI MARA CAWANGAN PERLIS STUDENTS - Wan Nurshazelin Wan Shahidan; Nor Azriani Mohamad Nor; Siti Nor Nadrah Muhamad; Azlan Abdul Aziz; Nur Syuhada Muhammat Pazil (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The COVID-19 pandemic and the implementation of the lockdown had a significant impact on the country’s community life and economic stability, resulting in job losses, school and educational institution closures, and a loss of foreign investment. Implementing home teaching and learning (PdPR) entailed additional costs, such as purchasing internet access, which increased the financial burden on parents. Therefore, Unit Zakat, Sedekah, & Wakaf (ZAWAF) of Universiti Teknologi MARA (UiTM) Cawangan Perlis is responsible for providing immediate financial assistance to UiTM staff and students. ZAWAF has taken proactive action by introducing an online zakat assistance application in March 2020 as an alternative to traditional face-to-face interviews during the pandemic. However, receiving a large number of applications and numerous reasons why students apply for zakat assistance to be processed urgently has affected ZAWAF during the zakat evaluation process. The Analytical Hierarchy Process (AHP) method has been used to assist ZAWAF in classifying which zakat applicants are eligible to receive zakat assistance immediately and ranking the important factors. The results revealed that the less capable family had been the most important factor, having the highest judgment and getting the highest average ranking from the three experts interviewed by Zawaf. The AHP method can be used to determine the other factors that contribute to the eligibility of students to receive zakat assistance and can help ZAWAF speed up the process of distributing zakat assistance to eligible zakat recipients. Future research can be made using other factors, such as a history of receiving previous zakat assistance and subfactors for each criterion (factor) that can contribute to whether students are eligible to receive zakat assistance.